Insights and perspectives on the enigmatic alary muscles of arthropods - Laetitia Bataillé; Gaëlle Lebreton; Hadi Boukhatmi; Alain Vincent (Frontiers in Cell and Developmental Biology, 2024)
Three types of muscles, cardiac, smooth and skeletal muscles are classically distinguished in eubilaterian animals. The skeletal, striated muscles are innervated multinucleated syncytia, which, together with bones and tendons, carry out voluntary and reflex body movements. Alary muscles (AMs) are another type of striated syncytial muscles, which connect the exoskeleton to the heart in adult arthropods and were proposed to control hemolymph flux. Developmental studies in Drosophila showed that larval AMs are specified in embryos under control of conserved myogenic transcription factors and interact with excretory, respiratory and hematopoietic tissues in addition to the heart. They also revealed the existence of thoracic AMs (TARMs) connecting to specific gut regions. Their asymmetric attachment sites, deformation properties in crawling larvae and ablation-induced phenotypes, suggest that AMs and TARMs could play both architectural and signalling functions. During metamorphosis, and heart remodelling, some AMs trans-differentiate into another type of muscles. Remaining critical questions include the enigmatic modes and roles of AM innervation, mechanical properties of AMs and TARMS and their evolutionary origin. The purpose of this review is to consolidate facts and hypotheses surrounding AMs/TARMs and underscore the need for further detailed investigation into these atypical muscles.